2013
DOI: 10.1002/ejhf.30
|View full text |Cite
|
Sign up to set email alerts
|

Co‐morbidities in patients with heart failure: an analysis of the European Heart Failure Pilot Survey

Abstract: Aims Co‐morbidities frequently accompany heart failure (HF), contributing to increased morbidity and mortality, and an impairment of quality of life. We assessed the prevalence, determinants, regional variation, and prognostic implications of co‐morbidities in patients with chronic HF in Europe. Methods and results A total of 3226 European outpatients with chronic HF were included in this analysis of the European Society of Cardiology (ESC) Heart Failure Pilot Survey. The following co‐morbidities were consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
339
2
28

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(395 citation statements)
references
References 41 publications
26
339
2
28
Order By: Relevance
“…HF subjects typically suffer from a number of coexisting diseases that may influence the outcomes of care [2,3,15]. To the best of our knowledge, this is the first study (i) investigating a comprehensive search of comorbidities based on administrative data, (ii) assessing their impact on short-term survival, and (iii) trying to disentangle between mortality associated with HF from that due to all other causes through a relative survival approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HF subjects typically suffer from a number of coexisting diseases that may influence the outcomes of care [2,3,15]. To the best of our knowledge, this is the first study (i) investigating a comprehensive search of comorbidities based on administrative data, (ii) assessing their impact on short-term survival, and (iii) trying to disentangle between mortality associated with HF from that due to all other causes through a relative survival approach.…”
Section: Discussionmentioning
confidence: 99%
“…HF is commonly accompanied by a broad range of comorbidities, with chronic kidney disease, anaemia and diabetes being the most prevalent, which further complicate the management of care, unfavourably affecting prognosis [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…16 Of note, the prevalences of the two commonest comorbidities, hypertension and diabetes, in our study were similar to that report; this is not the case for AF, which was twice as common in the present study. 16 Patients with more than three comorbidities have a higher risk of death and HF hospitalization, as shown by van Deursen et al, 23 although in their study only noncardiovascular comorbidities were analyzed. Another study, on incident HF, reported that patients with HFpEF were more likely to have both cardiac and non-cardiac comorbidities.…”
Section: Discussionmentioning
confidence: 92%
“…The protocol can easily be applied in other clinically-relevant models (e.g. models of diseases known to be associated with increased risk of AF, such as aging and hypertension, heart failure, or obesity [8,[13][14][15]), or in animals treated with drugs commonly used in AF patients.…”
Section: Perspectivesmentioning
confidence: 99%